Portrait of a Caregiver: Ethnodrama Development and Its Influence on Caregiver Well-Being. (19th October 2019) - Eaton, Jacqueline; Madsen-Wilkerson, Nancy
Abstract: Background and Objectives: The majority of long-term care needs are placed upon family members who often receive minimal support. In this study, we collaborate with family caregivers to create an ethnodrama about their experience and assess outcomes of participation, including caregiver well-being. Methods: Participants met over 4 months to discuss their roles as informal caregivers. Discussions were analyzed in a two-phase process and themes were developed into a script. Member checks included script review and revisions, culminating in viewing a professional performance of the play followed by a post-performance discussion and reflection. Data were gathered at six timepoints to assess caregiver well-being and longitudinal analysis was used to assess change during the course of the intervention. Results: Twenty-two caregivers completed intervention activities. Participant reactions to the process evolved overtime, from an initial hesitance about what individuals had to offer leading to an acknowledgement of feeling heard and a desire to help others. Caregivers had high levels of burden and positive perceptions towards caregiving. Those with high levels of self-rated health had the lowest levels of burden and the most positive perceptions of caregiving. Discussion and Implications: Developing an ethnodrama in partnership with caregivers is a unique and feasible method of caregiver support, mentoring, reflexivity, and meaning making. Promoting caregiver health early in the caregiving trajectory has the potential of reducing burden and elevating positivity towards caregiving.